Progressive changes in arch width from primary to early mixed dentition period: A longitudinal study - S Sangwan; H S Chawla; A Goyal; K Gauba; U Mohanty (Wolters Kluwer Medknow Publications, 2011)
Objective: The present study was conducted to evaluate, on a longitudinal basis, the changes in intercanine and intermolar widths form the primary to the early mixed dentition periods. Materials and Methods: A total of 38 children aged 4-5 years, with normal occlusion without any proximal caries or any dental anomalies, were selected. The impressions were recorded and casts were prepared. Intercanine and intermolar widths were measured on these dental casts with the help of a digital vernier calliper. After 3 years follow-up, the impressions were recorded again and dental casts were prepared. Intercanine and intermolar widths were measured again at this stage and were compared with the baseline data using the paired t-test and the chi square test. Results: There is a significant increase in the intercanine (3.93 + 1.70 mm) and intermolar width (1.49 + 1.77 mm) during the transition period from primary to early mixed dentition in both the arches and both the sexes. The gender-wise comparison showed a greater increase in males than in females, but this was not statistically significant. Conclusion: A thorough knowledge of growth changes during various stages of the mixed dentition period are important for a pediatric dentist to make an accurate diagnosis and treatment planning during preventive and interceptive orthodontics.